Pengaruh Brand Personality Terhadap Minat Beli Produk Body Mist (Studi pada The Body Shop di Trans Studio Mall Bandung) - Agnes Naibaho; Ai Lili Lili Yuliati (Jurnal Computech & Bisnis (e-Journal), 2017)
This research is influenced by the problems related to the brand personality on The Body Shop’s Body Mist product. Those problems based on the results of pre-survey showed that brand personality of The Body Shop’s Body Mist product that consists of sincerity, excitement, competence, sophistication and ruggedness has not yet been fully received good response from respondents. In addition, although The Body Shop’s Body Mist product received the title of Top Brand of the year 2015 - 2016, Top Brand Index value of The Body Shop’s Body Mist product fell in 2016. This shows that the power of the brand personality The Body Shop’s Body Mist product also decreased, because the brand personality is a form factor the first parameter to measure the value of the percentage of TBI, which is top of mind brand awareness. This study aims to determine the influence of the brand personality which consist of sincerity, excitement, competence, sophistication and ruggedness towards purchase intention. The results shows that the brand personality and purchase intention is in good category. The results of multiple regression analysis addressing sub variable competence, sophistication and ruggedness significantly influence the purchase intention, and the coefficient of determination shows that the brand personality variables significantly influence the purchase intention by 54,5%, and 45,5% are influenced by other variables outside of this research.  Keywords: brand personality, purchase intention,  the body shop’s body mist product